Association between tetrodotoxin resistant channels and lipid rafts regulates sensory neuron excitability - Alessandro, Pristerà (Public Library of Science (PLoS), 2018)
Voltage-gated sodium channels (VGSCs) play a key role in the initiation and propagation of action potentials in neurons. Na(V)1.8 is a tetrodotoxin (TTX) resistant VGSC expressed in nociceptors, peripheral small-diameter neurons able to detect noxious stimuli. Na(V)1.8 underlies the vast majority of sodium currents during action potentials. Many studies have highlighted a key role for Na(V)1.8 in inflammatory and chronic pain models. Lipid rafts are microdomains of the plasma membrane highly enriched in cholesterol and sphingolipids. Lipid rafts tune the spatial and temporal organisation of proteins and lipids on the plasma membrane. They are thought to act as platforms on the membrane where proteins and lipids can be trafficked, compartmentalised and functionally clustered. In the present study we investigated Na(V)1.8 sub-cellular localisation and explored the idea that it is associated with lipid rafts in nociceptors. We found that Na(V)1.8 is distributed in clusters along the axons of DRG neurons in vitro and ex vivo. We also demonstrated, by biochemical and imaging studies, that Na(V)1.8 is associated with lipid rafts along the sciatic nerve ex vivo and in DRG neurons in vitro. Moreover, treatments with methyl-β-cyclodextrin (MβCD) and 7-ketocholesterol (7KC) led to the dissociation between rafts and Na(V)1.8. By calcium imaging we demonstrated that the lack of association between rafts and Na(V)1.8 correlated with impaired neuronal excitability, highlighted by a reduction in the number of neurons able to conduct mechanically- and chemically-evoked depolarisations. These findings reveal the sub-cellular localisation of Na(V)1.8 in nociceptors and highlight the importance of the association between Na(V)1.8 and lipid rafts in the control of nociceptor excitability.